Trafficking of human beings for forced labour in EU member states: challenges in ringing charges and prosecuting cases in Bulgaria and Romania - Semkina, Elīza (Riga Graduate School of Law, 2021)
The study focuses on trafficking of human beings for forced labor. One of the key causes of trafficking of human beings is the demand for the victims’ services and the products produced by their exploitation, which generates high profits. This necessitates a strong response from the criminal justice and judicial system. In this aspect, the European Union has established numerous regulatory and policy strategies, and funding initiatives. The study’s primary goal is to identify case law on trafficking of human beings for forced labor in Romania and Bulgaria, so as to examine the practice of bringing charges and investigating cases. However, based on the insufficient information and data available, it appears that there are few prosecutions for trafficking of human beings, much less for the purposes for forced labor
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Human rights; Bulgaria; Romania